(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
A randomized trial compared short-term integrative psychotherapy (12 sessions combining cognitive-behavioral, rational, and relaxation techniques) with traditional rational psychotherapy (10–12 sessions) in 121 inpatients with ICD-10 F40–F41 anxiety disorders. Integrative therapy reduced mean Hamilton Anxiety scores from 33.1 to 8.7, achieving remission-level anxiety (HARS < 10) in 84 % of patients, whereas rational therapy lowered scores from 32.9 to 18.8 with 28 % in remission. Both treatments normalized mild depressive symptoms, but global severity (CGI-S) was “healthy” in 72 % versus 30 % of cases, respectively. Integrative therapy shortened hospital stay by 13 days and cut direct costs more than ten-fold, with lower six-month relapse (4.5 % vs 14.8 %). These results endorse short-term integrative psychotherapy as a clinically and economically superior option for routine management of anxiety disorders.